New Findings On Gender: The Effects Of Employment Status On Suicide - Kposowa AJ; Aly Ezzat D; Breault K (Dove Medical Press, 2019)
Augustine J Kposowa,1 Dina Aly Ezzat,1 Kevin Breault2 1Department of Sociology, University of California, Riverside, CA, USA; 2Department of Sociology and Anthropology, Middle Tennessee State University, Murfreesboro, TN, USACorrespondence: Augustine J KposowaDepartment of Sociology, University of California, 900 University Ave, Riverside, CA 92521, USATel +1 951 456 5425Fax +1 951 827 5444Email augustine.kposowa@ucr.eduBackground and objectives: The purpose of the study was to evaluate the impact of gender and employment on suicide with the use of expanded unemployment statuses as covariates.Methods: Data were obtained from release 5 of the National Longitudinal Mortality Study, a prospective study of deaths in the United States. Proportional hazards regression models were fitted to the data based on follow-up from 1990 to 2011.Results: Unemployment was significantly associated with suicide (ARR=1.628, 95% CI=1.356, 1.954), and men had suicide deaths that were five times greater than women (ARR=5.104, 95% CI=4.565, 5.707), however when the sample was stratified by sex, the impact of unemployment on suicide was much higher among women (ARR=2.988, 95% CI=2.045, 4.366) than among men (ARR=1.393, 95% CI=1.131, 1.717).Conclusion: Contrary to many findings and gender assumptions, unemployed women in the U.S. have higher deaths from suicide than unemployed men. Discussion focused on explanations for gender disparities in unemployment.Keywords: suicide, unemployment, gender